The first Chinese case of Siddiqi syndrome caused by a homozygous FITM2 variant. Issue 3 (26th June 2022) - Lin, Yunting; Zhang, Wen; Li, Duan; Chen, Xiaodan; Lu, Zhikun; Li, Xiaojing; Li, Xiuzhen
Abstract : A. The family pedigree. B. Whole exome sequencing of the proband‐parent trio revealed c.611_612dupTG(p.M205*) variant of FITM2 gene as suspicious variant. C. Sanger sequencing confirmed that c.611_612dupTG(p.M205*) variant of FITM2 gene was homozygous in the proband, while the unaffected parents were heterozygous.